2021
DOI: 10.3390/w13030296
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Monitoring of Hydrodynamics and Surface Water Quality in the Sulejów Dam Reservoir, Poland

Abstract: The aim of this work is to evaluate core variables of the ecological potential of the Sulejów Reservoir (temperature distribution, flow velocities, and concentrations of selected indicators, e.g., phosphates, nitrates, the abundance of phytoplankton) using a three-dimensional hydrodynamic model, GEMSS-HDM (generalized environmental modeling system for surface waters), coupled with a water quality model, WASP EUTRO (GEMSS-WQM). The monitoring data necessary to build the model were obtained from two multiparamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…The retention time of each lake can vary according to its hydrologic management. Physical factors of lakes, such as differences in water temperature, upstream river inflow rate, and retention time, significantly affect the delivery and accumulation of thermal energy of water bodies [10,[52][53][54]. Particularly for PD, the average water temperature change in the surface layer and water depth is considered to be complex because mixing occurs inside the lake due to the flow of the Namhan River and the Bukhan River, which have different water temperatures during various periods [55].…”
Section: Stratification Intensity and Its Guiding Factorsmentioning
confidence: 99%
“…The retention time of each lake can vary according to its hydrologic management. Physical factors of lakes, such as differences in water temperature, upstream river inflow rate, and retention time, significantly affect the delivery and accumulation of thermal energy of water bodies [10,[52][53][54]. Particularly for PD, the average water temperature change in the surface layer and water depth is considered to be complex because mixing occurs inside the lake due to the flow of the Namhan River and the Bukhan River, which have different water temperatures during various periods [55].…”
Section: Stratification Intensity and Its Guiding Factorsmentioning
confidence: 99%
“…Hydrodynamics and water quality are the two characteristics of water environment. Using real measured data, so as to investigate the influence of hydraulic conditions on water quality, and then construct a coupling model of hydrodynamic-water quality to predict water environment, it is a key direction of international water environment research 7 9 . The hydrodynamic-water quality model can not only quantitatively describe the water environment system and the complex processes that occur within it, but also intuitively display the scope and degree of pollution impact on the layer of geographic information system, so as to provide decision-making basis for the early warning and prevention of water pollution accidents 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Surface water quality monitoring is essential to assess the impacts of anthropogenic activities and natural phenomena [1,2], but it is labor-intensive, time-consuming, and costly [3]. Several studies have demonstrated that using remote sensing for water quality evaluation has significant advantages for surface water quality monitoring [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%